INCREASING UMKM INCOME WITH POC INNOVATION FROM FISHERY WASTEWATER IN KEDUNGREJO BANYUWANGI - Pamungkas, Wisnu Jalu; Wulansari, Nanda; Romadhoni, Devita; Permana, Krisma Wanagisra Indah; Defvara, Muhammad Farel; Fauzi, Ahmad; ‘Azizi, Ahmad Muhajir; Zahiroh, Luluk Lailatul; Fitriani, Dewi Nur; Abror, Hadziqul (LPPM Univ. Ibn Khaldun Bogor, 2025)
Kedungrejo Village has great fishery potential and is a key icon in Banyuwangi Regency, leading to numerous fish-processing industries. However, industrial expansion has not been accompanied by proper waste management, resulting in environmental issues that affect local communities. This study explores the utilization of fishery wastewater to produce Liquid Organic Fertilizer (POC) as an innovative solution to these challenges. The research was conducted through the Student Community Service Program (Promahadesa) organized by the University of Jember. The implementation included socialization, training, mentoring, and marketing strategies to support local Micro, Small, and Medium Enterprises (UMKM) in processing fishery waste into valuable products. The study involved a trial-and-error method to determine the optimal composition of POC, testing its effectiveness on plant growth, and conducting laboratory analysis to ensure quality standards. The results indicate that the production of POC from fishery wastewater effectively reduces waste, provides an alternative solution to fertilizer scarcity, and increases the economic value of fishery by-products. Furthermore, the initiative fosters creativity among local communities, encouraging sustainable waste management and economic empowerment. This research highlights the importance of integrating waste management solutions into local industries to support environmental sustainability and improve UMKM income.